2017
DOI: 10.18468/estcien.2017v7n1.p95-102
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antifúngica de Sideroxylon obtusifolium frente a diferentes espécies de Candida sp.

Abstract: <p>Candidiase é uma infecção fúngica oportunista cuja prevalência no mundo é de 6,9 casos por 1000 pacientes. O aumento na utilização de drogas antifúngicas, nos últimos anos, tem causado resistência aos medicamentos disponíveis para o tratamento. O objetivo deste estudo foi investigar a atividade antifúngica de <em>Sideroxylon obtusifolium</em> em estirpes associadas à candidiase. Os testes <em>in vitro</em> foram realizados com o extrato bruto e frações orgânicas contra estirpes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Quixabeira leaves and barks: similar metabolites with therapeutic potential Phytochemical screening revealed a greater diversity of metabolite classes when using cachaça and water as solvent (Table 1). In phytochemical screening, classes of secondary metabolites of the species and related to pharmacological activities (anti-inflammatory, cicatrizing, antioxidant) were identified (Leite et al 2015;Araújo-Neto et al 2010, Silva et al 2017Aquino et al 2016. ) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quixabeira leaves and barks: similar metabolites with therapeutic potential Phytochemical screening revealed a greater diversity of metabolite classes when using cachaça and water as solvent (Table 1). In phytochemical screening, classes of secondary metabolites of the species and related to pharmacological activities (anti-inflammatory, cicatrizing, antioxidant) were identified (Leite et al 2015;Araújo-Neto et al 2010, Silva et al 2017Aquino et al 2016. ) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Mey., Araliaceae), the leaves exhibited pharmacological activities similar to those of their roots, thus providing a less impactant form of obtaining the medicinal drug (Wang et al 2009). While studies have shown that quixabeira bark has anti-inflammatory, antinociceptive and antioxidant action for the treatment of pain and inflammation (Araújo-Neto et al 2010;Leite et al 2015), the leaves also demonstrated anti-inflammatory and antinociceptive action, besides the antifungal action (Aquino et al 2016;Silva et al 2017). However, leaves are not used by the local communities.…”
Section: Introductionmentioning
confidence: 99%
“…Fazendo parte da microbiota de homens e animais, sendo conhecidos por degradarem proteínas e carboidratos para obterem carbono e nitrogênio, e devido a sua capacidade adaptativa, se desenvolvem tanto na presença de oxigênio quanto em anaerobiose. São classificadas como fungos patogênicos e estão associadas a uma variedade de infecções, desde superficiais até as invasivas, que se manifestam em diferentes regiões anatômicas na espécie humana (CORRÊA et al, 2018;SILVA et al, 2017).…”
Section: Introductionunclassified
“…Além de Candida albicans, há outras espécies de importância clínica, como Candida glabrata, Candida tropicalis, Candida parapsilosis e Candida krusei estão associadas à cerca de 90% dos casos de candidíases invasivas; enquanto, as espécies Candida guilliermondii, Candida lusitaniae, Candida kefyr, Candida famata, Candida inconspicua, Candida rugosa, Candida dubliniensis e Candida norvegensis, são relatadas com menos frequência. (FERREIRA et al, 2018;SILVA et al, 2017).…”
Section: Introductionunclassified